The people of the eye : deaf ethnicity and ancestry - Lane, Harlan L.; Pillard, Richard; Hedberg, Ulf. (New York ; Oxford : Oxford University Press, 2011)
What are ethnic groups? Are Deaf people who sign American Sign Language (ASL) an ethnic group? This book brings Deaf studies, history, cultural anthropology, genetics, sociology, and disability studies to bear as it compares the values, customs and social organization of the Deaf world to those in ethnic groups.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 11, 2011).
Keywords: Deaf -- United States -- History; Deafness -- Social aspects -- United States; Heredity; Ethnic groups